IMPLEMENTASI PRINSIP CHECKS AND BALANCES ANTARA BADAN PERMUSYAWARATAN DESA DENGAN PEMERINTAH DESA DALAM PENYUSUNAN PERATURAN DESA (Studi Kasus Desa Tegalombo, Kecamatan Tegalombo, Kabupaten Pacitan) - Ismail .; Sulton .; Prihma Sinta Utami (EDUPEDIA, 2018)
The great agenda of reform is the government system of the State of Indonesia in the form of decentralization that is a government that gives authority to the regions to manage their own households. The emergence of regional autonomy is marked by the issuance of Law No. 22 Th 1999, then revised into Law No. 32 Th 2004, and refined into Law No. 23 Th 2014. Regional autonomy gives authority to the village to manage the potential of the village owned by this is reinforced by the issuance of Law No. 6 Th 2014 About Village. The purpose of this research is; 1). To know the implementation of the checks and balances principle of the Village Consultative Body with the village government in drafting the village regulations, 2). To know the implementation of the checks and balances principle of the Village Consultative Body with the village government in the discussion of village regulations draft, 3). To know the implementation of the principle of checks and balances of the Village Consultative Body with the village government in determining the village regulation draft. The type of this research is qualitative research object in Tegalombo Village, Tegalombo District Pacitan Regency, the type of research used is case study, the procedure used to collect data is observation, interview, and documentation. Data analysis techniques used data reduction, data presentation, and conclusions. The results of this study are: 1). In the preparation of village regulation draft has not happened checks and balances because the formulation of village regulations is dominated by the village government where the Village Consultative Council is powerless to propose the draft of village regulations there are three factors that menyebapkan the empowerment of the Village Deliberation Agency include: Anggae Angotanya, weakness of political education resulting perception errors In relation to its position and duties, and the Village Consultative Body does not have administrative and kaitanya communication with its duties and authorities, 2). In the discussion of the village regulation draft, there have been no checks and balances since the Village Consultative Board has no effort to control the village regulation draft proposed by the village government. This empowerment is not permitted because BPD does not have a set of rules for the preparation of village regulations because it lacks political education 3) . In the determination of village regulations there has not been any checks and balances due to the regulations set forth although the Village Deliberative Council agreed but the approved draft regulation does not contain the following principles: protection, justice, equality, orderliness, and balance. The core has not been able to prosper the community as a whole.